2001
DOI: 10.1590/s0102-09352001000300011
|View full text |Cite
|
Sign up to set email alerts
|

Toxina T-2 e alterações do crescimento endocondral em frangos de corte

Abstract: Foi testada a habilidade da toxina T-2, produzida por Fusarium sporotrichioides Sherb e veiculada por milho experimentalmente contaminado, em induzir alterações da placa epifisária proximal do tibiotarso de frangos de corte. Pintos de um dia, todos machos e da linhagem Hubbard, foram alimentados com ração básica a base de milho e soja, na qual todo o milho foi substituído por milho contaminado, contendo exclusivamente T-2 na quantidade de 2,64mg/kg. Um outro grupo alimentado com milho não contaminado serviu co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It can produce toxic syndromes in humans or animals after ingestion of only tiny amounts, as low as micrograms or nanograms per gram of food (Mngadi et al 2008). Furthermore, it can destroy joint cartilage of chickens during the development and proliferation stage and can lead to OA (Nascimento et al 2001;Yang 1995). In China, KBD is an endemic form of OA that is characterized by joint thickening, deformation, short limbs, and dwarfism.…”
Section: Pathological Changes In Articular Cartilage Of Rat Treated Wmentioning
confidence: 99%
See 1 more Smart Citation
“…It can produce toxic syndromes in humans or animals after ingestion of only tiny amounts, as low as micrograms or nanograms per gram of food (Mngadi et al 2008). Furthermore, it can destroy joint cartilage of chickens during the development and proliferation stage and can lead to OA (Nascimento et al 2001;Yang 1995). In China, KBD is an endemic form of OA that is characterized by joint thickening, deformation, short limbs, and dwarfism.…”
Section: Pathological Changes In Articular Cartilage Of Rat Treated Wmentioning
confidence: 99%
“…Exposure is typically through contaminated food or grains (Mngadi et al 2008;Ueno 1984). T-2 toxin can cause lesions in hematopoietic, lymphoid, gastrointestinal, and cartilage tissues, especially in physeal cartilage (Nascimento et al 2001;Rosenstein and Lafarge-Frayssinet 1983). In vitro, T-2 toxin can induce aggrecan degradation in chondrocytes through inhibiting aggrecan synthesis and promoting aggrecanase and pro-inflammatory cytokine production .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an alteration in the organelles of these cells, such as mitochondria, endoplasmic reticules and Golgi complex, may be consequence of exogenous stimulus (as, drugs for example) (Amdur et al, 2001). Nascimento et al (2001) have demonstrated that metabolites isolated from isoflavonols, such as, the toxin T-2, could be responsible by the lesive effect observed in the condrocytes and vascular tissue of animals treated with soy extract (Nascimento et al, 2001). Simões et al (2007) have described that the flavonoids would be capable to influence some biological processes, including the mutagenic activity (Simões et al, 2007).…”
Section: Introductionmentioning
confidence: 99%